Titans double feature Clash of the Titans - Wrath of the Titans
Clash of the titans (2010, 106 min.): Born of a god but raised as a man, Perseus is helpless to save his family from Hades, vengeful god of the underworld. Battling unholy demons and fearsome beasts, Perseus and his warriors will survive only if Perseus accepts his power as a god, defies fate and creates his own destiny.
Wrath of the titans (2012, 99 min.): A great war has erupted between the gods. Perseus is brought out of retirement to once again become a hero in order to find Zeus and end the titans' struggle to rule the earth.
Clash of the titans -- Wrath of the titan
In English, French or Spanish with optional subtitles in English, French or Spanish.
Keywords: Perseus (Greek mythology) -- Drama